Comparison of physicochemical properties of barracuda (Sphyraena barracuda Edwards, 1771) skin collagen hydrolyzed using two different pepsin sources - Leshanthiy A/P K Santhi Rasegaran a; Abdul Aziz Jaziri; Ahmad Hazim Abdul Aziz; Rossita Shapawi; Ruzaidi Azli Mohd Mokhtar; Wan Norhana Md. Noordin; Rahmi Nurdiani; Nurul Huda (Indonesian Society for Knowledge and Human Development, 2024)
This research focused on the comparison of extractability and physicochemical properties of barracuda (Sphyraena barracuda Edwards, 1771) skin collagens prepared using pepsins from bovine (PSC-B) and porcine (PSC-P). The PSC-P sample had a significantly higher (p<0.05) collagen extractability (31.16%) compared to the BCPB (19.48%). Based on the Sodium dodecyl-sulfate polyacrylamide gel electrophoresis (SDS-PAGE) profiles, all hydrolyzed collagens were identified as a type I collagen with two different alpha chains (α1 and α2). The Infrared spectra showed that the collagen's triple-helical structure was maintained in the PSC-B and PSC-P samples, as mostly reported from other literatures. In terms of the thermal stability, the value of BCP-B (43.63°C) was greater than that of BCP-P ( = 37.49°C), and their values were comparable to other literatures related on marine fish skin collagens. Overall, the by-product skin of barracuda (S. barracuda Edwards, 1771) can be utilized for alternative collagen products.